Comment on: "On the effect of room temperature ageing of Ni-rich NiTi alloys". (October 2016) - Cui, Jian
Abstract: Kustov et al. published a paper (Scripta Mater. 103 (2015) 10–13) in which they claimed the martensitic transformation of Ni-rich TiNi alloys can be strongly modified by a room-temperature aging process for a relative short time. To clarify the effect of room-temperature aging on the martensitic transformation of Ni-rich TiNi alloys, a systematic differential scanning calorimetry study with a long room-temperature aging process (1109 days) was performed. According to this study, we show that the data presented in the commented paper are not representative. The effect of room-temperature aging was apparently overemphasized by 2 orders of magnitude.